Social Service and Community Social Worker Program for Empowerment Homeless and Beggars in Yogyakarta - Herpita Wahyuni; Suswanta Suswanta; Danang Eko Prastya (Jurnal Studi Sosial dan Politik, 2021)
This study aims to determine the Social Service and Community Social Workers efforts to empower the homeless and beggars in Yogyakarta. Data analysis techniques with NVivo 12 Plus software helps in efficient qualitative research. This research focuses on the Office of Social Affairs and Community Social Workers empowering the homeless and beggars in Yogyakarta. The data used are primary data through interviews with the Office of Social Affairs and Community Social Workers and secondary data from various documents on the empowerment of girdles and beggars. The results reduced social disparities with multiple activities: counselling, counselling, training, and policing—Office of Social Affairs and Community Social Workers. The Office of Social Affairs and Community Social Workers provide training such as screen printing, haircuts; if the beggar is still a teenager, then he is put in a youth development centre and fostered within three to four days; training activities are in the form of making various types of handicrafts. Counselling and counselling in reducing the number of beggars and homeless people in Yogyakarta have been going well. Homeless people and beggars are regulated in the Yogyakarta Special Region Regulation Number 1 of 2014, prohibiting money from homeless people and beggars.